2018
DOI: 10.1177/0956462418796088
|View full text |Cite
|
Sign up to set email alerts
|

Burden of genital warts in Peru: an observational study

Abstract: Genital warts (GW) are mucosal or skin lesions caused by sexual transmission of human papillomavirus (HPV). This study estimates the frequency of GW cases in physicians’ clinics and physicians’ usual practices of GW referral and diagnosis in Peru. Participants in this study were a convenience sample of 100 physicians in five specialties: primary care (17), gynecology (37), urology (10), dermatology (31), and infectious diseases (5). Physicians completed a survey and daily log of all patients aged 18–60 years s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…The prevalence rates found are high, similar to that reported in Mexico (5.10%), Hungary (4.03%) and the USA (4.10%), and much higher than that in most countries, such as Italy (0.05%), Canada (1.10%) [ 22 ] and Vietnam (0.20%); the peak incidence in the young population occurred between the ages of 18 and 29 years [ 1 , 23 ].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The prevalence rates found are high, similar to that reported in Mexico (5.10%), Hungary (4.03%) and the USA (4.10%), and much higher than that in most countries, such as Italy (0.05%), Canada (1.10%) [ 22 ] and Vietnam (0.20%); the peak incidence in the young population occurred between the ages of 18 and 29 years [ 1 , 23 ].…”
Section: Discussionsupporting
confidence: 72%
“…Data regarding the prevalence of genital lesions in men from low/middle income countries are scarce [ 1 , 24 26 ]. These studies used different epidemiological and analytical methodologies, which could explain the differences in prevalence: 5.25% in Peru [ 1 ], 1.22% in India [ 24 ] and 1.99% in Mexico [ 25 ]. The incidence reported in Mexico was 42%, and that in Brazil was 31.9% over a period of four years [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of a 2007 study of women aged 18–45 years in 4 northern European countries over a 12-month period showed a GW prevalence of 1.3% in Denmark, 1.9% in Iceland, 1.1% in Norway, and 1.0% in Sweden [31]. A recent study performed in Peru using the same methodology reported also similar prevalence rates [32].…”
Section: Discussionmentioning
confidence: 96%
“…Otra patología frecuente que también tiene impacto en la morbilidad de las mujeres son las verrugas genitales, que generalmente están asociadas a subregistro; la prevalencia es 2,28% (IC95% 2,02 a 2,56) en Perú y aparentemente son casos frecuentemente vistos en los consultorios médicos (27) .…”
Section: Discussionunclassified